Proto-Bantu Reflexes in Dhaisu - Ngonyani, Deo; Biersteker, Ann; Kioko, Angelina Nduku; Rugemalira, Josephat (My University, 2022)
This paper is a study of Proto-Bantu reflexes in Dhaisu, a highly endangered language also known as Dhaiso, Segeju, Daisu and Kidhaisu (dhs, E56). Dhaisu is spoken in the East Usambara Mountains in northeastern Tanzania, but its closest relative is Kamba (E55). Seven vowels are reported in this study as has been in other studies /i, ɪ, ɛ, a, ɔ, ʊ, u/. However, no contrast can be established between ɪ and ɛ, or between u and ʊ. The data show that Dhaisu vowel system is changing to a 5-vowel system *i̧, *i, *e, *a, *o, *u, *u̧ > /i, ɛ, a, ɔ, u/. The most remarkable feature of this change is that unlike other Bantu languages, which merge the mid-high to high vowels, Dhaisu is merging the mid-high vowels to mid-low. The innovation is demonstrated in (a) numerous lexical items in which Proto-Bantu *i has become ɛ, and PB *u has become ɔ; (b) several nominal prefixes that are constructed in PB having mid-high vowels now have mid-low vowels, and (c) the applicative suffix whose PB form was *id is now -ɛr in Dhaisu. The fact that the change does not seem to have affected all nominal prefixes with mid-high vowels, and has affected not all verbal derivation with mid-high vowel suggests an ongoing transition. Reflexes of consonants are presented to show that they are not a result of spirantization.
Keywords: Proto-Bantu; Dhaisu; Vowels